Minimization of Nickel Slag Waste as an Alternative Gravel Material in Green Concrete Mixtures - Taufieq, Nur Anny Suryaningsih; Ahmad, Irma Aswani; Pertiwi, Nurlita (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. The main issue addressed in this study is the use of environmentally unfriendly concrete materials, such as gravel, which is a non-renewable resource. In addition, the production of cement used in concrete also contributes to air pollution. Therefore, innovation in more environmentally friendly construction materials is necessary, one of which involves using nickel slag waste as a partial replacement for coarse aggregates in green concrete. The proposed solution is the utilization of nickel slag, a by-product from the nickel smelting industry, as an alternative material to replace gravel in green concrete mixtures. This study aims to determine the optimum percentage of nickel slag as a substitute for gravel that can produce concrete with sufficient strength while maintaining environmental friendliness. The methods used in this research include testing the physical and chemical characteristics of nickel slag, producing concrete specimens with varying percentages of nickel slag, and conducting mechanical property tests such as compressive strength and slump tests to assess the performance of the resulting green concrete. The results show that using up to 50% nickel slag as a replacement for gravel in green concrete leads to a decrease in compressive strength, although the reduction is not significant. Additionally, the use of nickel slag can reduce the environmental impact of the construction industry by utilizing waste that had previously been underutilized. The application of nickel slag as a partial replacement for coarse aggregates in green concrete offers a promising solution for creating more sustainable construction materials. Keywords: green concrete, nickel slag, coarse aggregate, compressive strength, environmentally friendly